Bibliometric Analysis of Islamic Macroeconomic Publication Trends Using VOSviewer - Rozalinda, Rozalinda; Augusna, Wahyuni Lely; Wira, Ahmad; Azis, Saipul (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2024)
This research aims to analyze the topics of articles published in Google Scholar and Dimensions journals with the keyword